EVALUASI ADRs (ADVERSE DRUG REACTIONS) PADA PASIEN ASMA RAWAT INAP DI RUMAH SAKIT X KUDUS - Setyoningsih, Heni; Apriliyani, Shelli; Wijaya, Hasty Martha (Journal Pharma Saintika, 2025)
Asthma is a chronic inflammatory disorder of the respiratory tract. Adverse drug reactions (ADRs) are responses to adverse and unwanted drugs that occur at doses normally used in humans for the prevention, diagnosis, or therapy of disease or for physiological function modification. The purpose of this study was to determine the type of therapy that was often used and to determine the number of ADRs in asthma patients hospitalized at X Hospital in 2021. This study was an observational study using a non-experimental descriptive method with retrospective data collection. The data was taken from medical record searches and side effects monitoring sheet. The patients in the inclusion criteria were 42 patients; their data were processed statistically using univariate analysis with a frequency test. The results showed that the types of therapy that were often used in the treatment of asthma were topical therapy 51 (35.7%), parenteral therapy 49 (34.3%), while oral therapy was 43 (30.1%). As well as the number of ADRs (Advers Drug Reactions) with complaints of chest palpitations and tremors on salbutamol treatment as many as 4 patients (23.5%), nausea, vomiting on aminophylline treatment as many as 4 patients (23.5%), digestive disorders on methylprednisolone as many as 2 patients (11.8%), and the incidence of dry or painful mouth and throat, hoarseness on ventolin nebulizer treatment was 7 patients (41.2%).